Settling of silicon carbide particles in cast metal matrix composites - Ourdjini, A.; Chew, K. C.; Khoo, B. T. (Elsevier BV, 2001)
The success of metal matrix composites as potential materials for the manufacture of engineering components depends on closer control of their microstructure during processing. One of the important factors influencing the microstructure is settling of the particles during liquid processing of these composites. In this paper settling of SiC particles in cast aluminium alloy metal matrix composite was studied as function of particle size, weight fraction and melt temperature during isothermal holding and solidification experiments. Isothermal holding of A356 aluminium alloy reinforced with 20wt.% of silicon carbide particles showed that settling occurs at significantly slower rates than predicted by theoretical models. The results also showed that the melt temperature appears to have a slight effect on the settling behaviour. Experiments on settling during mixing and solidification revealed that at low melt temperatures the volume fraction of particles does not affect the rate of settling but as the melt temperature increases the particles tend to settle when present in lower volume fractions.